2015
DOI: 10.3168/jds.2014-8982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatments for claw horn lesions in dairy cows in a randomized controlled trial

Abstract: Lameness is one of the most significant endemic disease problems facing the dairy industry. Claw horn lesions (principally sole hemorrhage, sole ulcer, and white line disease) are some of the most prevalent conditions. Despite the fact that thousands of animals are treated for these conditions every year, experimental evidence is limited on the most effective treatment protocols. A randomized, positively controlled clinical trial was conducted to test the recovery of newly lame cows with claw horn lesions. Ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
104
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 15 publications
(17 reference statements)
5
104
1
4
Order By: Relevance
“…Additionally, previous work has demonstrated increased new bone growth on the flexor tuberosity of the distal phalanx in cows that have suffered more lameness and CHDL throughout life, and one possible mechanism for this new bone growth is inflammation in the surrounding soft tissues with CHDL (Newsome et al, 2016). Previous work has also shown that combining the administration of nonsteroidal anti-inflammatory drugs with applying a block to the nonaffected claw improved recovery rates for lameness in acute cases of disease (Thomas et al, 2015). The fact that the sole soft tissues appear to have been inflamed when a sole ulcer was present, and the potential detrimental effects this has on the surrounding anatomical structures such as the flexor tuberosity, highlights the importance first of prevention, and second of early detection and effective treatment of lame cows, which current evidence suggests should include the administration of nonsteroidal anti-inflammatory drugs and the application of a block to the nonlame claw.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous work has demonstrated increased new bone growth on the flexor tuberosity of the distal phalanx in cows that have suffered more lameness and CHDL throughout life, and one possible mechanism for this new bone growth is inflammation in the surrounding soft tissues with CHDL (Newsome et al, 2016). Previous work has also shown that combining the administration of nonsteroidal anti-inflammatory drugs with applying a block to the nonaffected claw improved recovery rates for lameness in acute cases of disease (Thomas et al, 2015). The fact that the sole soft tissues appear to have been inflamed when a sole ulcer was present, and the potential detrimental effects this has on the surrounding anatomical structures such as the flexor tuberosity, highlights the importance first of prevention, and second of early detection and effective treatment of lame cows, which current evidence suggests should include the administration of nonsteroidal anti-inflammatory drugs and the application of a block to the nonlame claw.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be important to prevent the occurrence of the first lifetime lameness event, although based on this analysis it is not possible to know whether it was the first lifetime lameness event or some other environmental or animal-based interaction that is important in consigning a cow to repeat lameness events. In addition, findings from this study highlight that early and effective treatment of lameness reducing the likelihood of recurrence or cases becoming chronic (Thomas et al, 2015) may also be crucial to lameness control at a herd level.…”
mentioning
confidence: 89%
“…The Agriculture and Horticulture Development Board Dairy 0 to 3 mobility 3 scoring system was used, which is the UK industry standard (Thomas et al, 2015). Cows were observed from behind during unrestricted walking in the passageways where cows were housed.…”
Section: Locomotion Assessmentmentioning
confidence: 99%
“…The 2 observers had been trained using this locomotion scoring system and had used the system during previous research studies ( Thomas et al, 2015Thomas et al, , 2016. Inter-observer tests were performed as follows: 176 cows were locomotion scored by both observers during the same passage of walking.…”
Section: Locomotion Assessmentmentioning
confidence: 99%